The Effect of Training and Competency on Shipping Safety Performance (Study at Tanjung Emas Port Semarang) - Ignatius Martanto; Rauly Sijabat (Politeknik Kelautan dan Perikanan Dumai, 2022)
Shipping safety performance cannot be separated from the quality of sea transportation. The performance of sea transportation safety is a very important factor because it is related to the efforts of the Directorate General of Sea Transportation in realizing effective and efficient sea transportation. Human resources are one of the factors that cause shipping safety performance is not optimal. The results of this study indicate that the problems that occur in shipping safety performance are caused by the competency factor of the workers on board that are not yet optimal. In connection with this phenomenon, this study intends to empirically examine the effect of training and competence on shipping safety performance. Related to this objective, data on training, competence and performance of shipping safety was collected through interviews using questionnaires to workers on board ships at Tanjung Emas Port, Semarang. The data obtained were then analyzed using the Structural Equation Modeling approach to test the research model and the influence between variables. The results of this study indicate that the performance of shipping safety is caused by the competence factor of the above workers when it is not optimal. In addition to competence, this study also shows that problematic shipping safety performance is caused by low training factors. This study also shows that the provision of training can shape and build the competencies needed to support shipping safety performance.